The impact of quality awareness on quality results of manufacturing firms: The mediating effect of total quality management - Rauf, Nurhayati (Archives of Business Research, 2018)
This study highlights the important role of quality awareness for each company in implementing total quality management in producing quality results that is in accordance with consumer desires. This study aims to analyze the effect of quality awareness on total quality management and quality results. The research was conducted at manufacturing firms in the Makassar industrial area (KIMA). The unit of analysis used is a company that has implemented total quality management, namely as many as 40 companies. Respondents are managers or staff that represents each company. Data were analyzed using Partial Least Square (SmartPLS). The results of the study provide evidence that, (1) quality awareness has a positive significant effect on total quality management; (2) quality awareness has a positive insignificant effect on quality results; (3) total quality management has a positive significant effect on quality results; and (4) quality awareness has a positive significant effect on quality results through total quality management.